IMPLEMENTASI PEMBERIAN BANTUAN HUKUM KEPADA MASYARAKAT TIDAK MAMPU MELALUI POSBAKUM DI PENGADILAN AGAMA JAYAPURA - Kurniawati, Laili Shofiya; Sugimin, Sugimin; Lakarim, Rahmat (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
Supreme Court Circular Letter (SEMA) Number 10 of 2010 which is currently changed to Supreme Court Regulation (PERMA) Number 1 of 2014 concerning Legal Aid Services to underprivileged people in the Courts. By seeing this, the Jayapura Religious Court is required to be as much as possible to implement the rule.. Therefore, this research will see how the implementation that has been implemented by the Jayapura Religious Court and the obstacles in implementing the regulation. The research used is qualitative research by looking at a case study in the Court institution. Where the data is obtained through observation, interviews, and documentation, which then the data will be analyzed using laws and regulations. The results of the study suggest that in implementing the Regulation on the provision of legal assistance to underprivileged people, it has not run optimally because there are several obstacles faced by the Jayapura Religious Court, including first, budget constraints that have not been accommodated by the entire poor in need. Second, public knowledge related to the Legal Aid Post (POSBAKUM) in the Jayapura Religious Court is still low. And the third, the lack of Legal Aid Institutions to manage Legal Aid Posts (POSBAKUM) in the Field of Islamic Civil Affairs.